Do policy mix characteristics matter for electric vehicle adoption? A survey-based exploration. (October 2020) - Li, Lixu; Wang, Zhiqiang; Wang, Qiang
Highlights: Explore the impacts of policy mix characteristics on electric vehicle adoption. Emphasize the moderating roles of the consistency of policy mixes. Expand the theory of planned behavior from a policy mix perspective. Survey data from 927 participants in China. Managerial implications for policymakers are highlighted. Abstract: Policy mixes that combine multiple policy instruments together are proposed as methods to accelerate the adoption of electric vehicles (EVs). This paper examines the links among psychological factors, policy mix characteristics, and EV purchase intention based on an extended theory of planned behavior (TPB). The empirical results from a survey in China reveal that the consistency, coherence, and credibility of policy mixes matter greatly in increasing an individual's EV purchase intention, whereas comprehensiveness has a non-significant effect. More importantly, the consistency negatively moderates the effects of consumer attitude, subjective norm, and personal norm on purchase intention, but positively moderates the relationship between perceived behavioral control and purchase intention. This paper makes theoretical contributions by extending the TPB from a policy mix perspective, which provides new knowledge for both policy research and EV adoption literature. The findings also have policy implications for the adoption of EVs.